Soil properties and available sulphur variability under irrigated and rainfed cotton in Bara tract of Bharuch, Gujarat - KUMAR, SHRVAN; DAS, AMARESH; CHINCHMALATPURE, ANIL R. (Journal of Soil and Water Conservation, 2020)
Soil properties and available sulphur status of soils under irrigated and rainfed cotton system were investigated from Bara tract comprising Amod, Vagra and Jambusar talukas of Bharuch district, South Gujarat. In surface layer, soil pH, EC, CEC and organic C ranged from 7.1-8.9, 0.12-2.70 dS m-1, 33.6-59.6 cmol (p+) kg-1 and 0.18-0.86 per cent, respectively in irrigated soils, while similarly for rainfed soils corresponding values were 6.7-9.0, 0.16-1.61 dS m-1, 34.6-56.1 cmol (p+) kg-1 and 0.08-0.65 per cent, respectively. Results revealed that surface layer of irrigated (20.0 %) and rainfed (37.5 %) soils exhibited ‘low’ status of available S in three talukas. Surface layer had higher values of organic C and available S than sub-surface layer in both systems, while irrigated soils had higher values than rainfed soils. To overcome ‘low’ S status in soils by use of inorganic/ organic sources or manures like sulphonated compost/bio-composts would be beneficial for higher cotton production under both systems.